An unusual case of severe hyperbilirubinemia and thyrotoxicosis - Jain Mohak; Shastri Minal; Patel Nilay; Dobariya Riya; Sirajwala Abulkalam (Endocrine Regulations)
Objective. We report a case of a 23-year-old pregnant female with five months of amenorrhea. She was referred to us with rapidly developing jaundice, anemia, and dyspnea with hyperthyroidism.